PEMANFAATAN DATA GEOMETRI SUNGAI UNTUK ANALISIS PETA DAERAH GENANGAN BANJIR SEBELUM DAN SETELAH DIBANGUN FLOODWAY PLANGWOT-SEDAYU LAWAS (Studi Kasus Wilayah Sungai Bengawan Solo Bagian Hilir) - , NOVIANINGRUM EKARINA SUDARYANTO; , Ir. Waljiyanto, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Flood is an event when the land is submerged by water. Events of flood often arise when heavy rainfall occur, which increase the discharge flow and exceeds the capacity of the river. Flood is an annual disaster happen across Indonesia. Hence it is needed a course to control over flood. Floodway (designed canal for flood) is one way to control flood. It is expected that building a floodway will decrease the inundated area. This study aimed to review how effective a floodway construction to the changing inundated area of the river area. Case study of the floodway constructed in the downstream of Bengawan Solo river basin. This research use eight (8) measurement points for data processing. The point selection based on the coverage area before and after the construction of the Plangwot-Sedayu Lawas floodway. Data processing use to know the changing of the inundated area after construction of the floodway use HEC RAS and ArcView 3.1 software. This data processing was divided into 2 (two) scenarios of hydraulics model, the hydraulic model before (1994) and after the construction of floodway (2011), with flood return period (Q) of 10 years, Q20 and Q50. In general, between 1994 to 2011 (within the period of 17 years) there has been a reduction in flood inundation area. This is evident from the reduction in flood inundation areas on land use in the local area. A reduction on the Q10 (a 10 years flood return period) flood area cover 543.71 hectares, from the total inundation area of 14.341.28 hectares in 1994 to 13.797.57 hectares in 2011. A reduction on the Q20 (a 20 years flood return period) flood area cover 5.322.78 hectares, from the total inundation area of 19.382.71 hectares in 1994 to 14 059.93 hectares in 2011. A reduction on the Q50 (a 50 years flood return period) flood area cover 5.893.36 hectares, from the total inundation area of 20.406.87 hectares in 1994 to 14.513.51 hectares in 2011. The reduction in the flood inundation area, indicates that floodway Plangwot-Sedayu Lawas effectively considered for flood control on the downstream of Solo River Basin.